Study derivational building in ukrainian affixoids language in the content of training future philologists (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article discloses a derivative affixoids potential in the Ukrainian language in the content of training future philologists: status affixoids influence in strengthening affixoids aglyutinativnyh trends in the Ukrainian language. A system of tasks aimed at the study of potential diversion affixoids in the content of academic disciplines scientific subject training.
Keywords: affixoids; prefiksoid; suffiksoid; derivational potential future teachers philological specialties